Not Our Thucydides? Identifying the Strategos at history 1.117 - Luginbill, Robert D. (Classica et Mediaevalia, 2023)
The Thucydides mentioned at History 1.117 as being one of the three strategoi in command of the reinforcement sent to reinforce Pericles’ siege of Samos in 439 was most likely the author of the history. No other known likely candidates exist, and the objections to considering the historian are based upon flawed conjectural readings of the internal evidence of the History.